Facile Fabrication of Electrohydrodynamic Micro‐/Nanostructures with High Aspect Ratio of a Conducting Polymer for Large‐Scale Superhydrophilic/Superhydrophobic Surfaces. Issue 2 (29th November 2017) - Lv, Guowei; Liu, Yuhang; Shao, Jinyou; Tian, Hongmiao; Yu, Demei
Abstract: This communication describes a straightforward, cost‐effective, and contactless lithography technique, electrohydrodynamic patterning, for fabricating the high‐aspect‐ratio micro‐/nanostructures of the conducting polymer (CP) films directly on a conductive substrate with high integrity and throughput. Meanwhile, the superhydrophilicity/superhydrophobicity of the final CP films can be obtained by modulating the ON/OFF‐state of the circuit of the assembly in the structure formation process. The final patterned CP films are hydrophilic/superhydrophilic when the circuit of the assembly is ON‐state in the structure formation process, while they are hydrophobic/superhydrophobic when the circuit of the assembly is OFF‐state. The high‐aspect‐ratio micro‐/nanostructures of the CP films with the superhydrophilic/superhydrophobic surface are important in both fundamental research and practical applications such as photovoltaics, sensors, supercapacitors, actuators, low friction surfaces, and water harvesting. Abstract : The high‐aspect‐ratio micro‐/nanostructures of the conducting polymer films can be fabricated directly on a conductive substrate with high integrity and throughput via electrohydrodynamic patterning and, meanwhile, the superhydrophilicity/superhydrophobicity of the final patterned conducting polymer films can be achieved by variating the upper/lower electrode of the capacitor‐like experimental installation and thus modulating the ON/OFF‐state of the circuit in the structure formation process.